2022
DOI: 10.3390/app12104925
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Temperature on the Vein Wall Based on the Analysis of the IR Signal during Endovasal Laser Treatment

Abstract: Possibility of controlling the temperature of the vein wall during endovasal laser treatment (EVLT) is investigated. The desired medical effect is achieved by the coagulation of the vein wall at the temperature of 80 °C. Heating of the vein wall is mainly due to the efficient conversion of laser radiation into heat in an optothermal fiber converter (OTFC) located at the output end of the optical fiber placed inside the vein. Titanium-containing optothermal fiber converter (TOTFC) is very promising for EVLT app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Where, the study concluded that the longer wavelength is preferred to be used in thin-walled veins with low applied laser power. 21 Developed a thermophysical model of EVLA. This model depended on the controlling of the applied laser power according to the heat of veins.…”
Section: Introductionmentioning
confidence: 99%
“…Where, the study concluded that the longer wavelength is preferred to be used in thin-walled veins with low applied laser power. 21 Developed a thermophysical model of EVLA. This model depended on the controlling of the applied laser power according to the heat of veins.…”
Section: Introductionmentioning
confidence: 99%